INITIATION OF BALANCED ENVIRONMENTAL ASPECTS of SMEs PERSPECTIVE STRATEGIC MANAGEMENT APPROACH QUADRUPLE HELIX INNOVATION MODEL (QHIM) - Harminingsih Harminingsih; Kumaratih Sandradewi; Andriani Kusumaningrum; Harsanto Harsanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The prolonged covid-19 pandemic entering its third year has created turbulence, which has resulted in various conditions that must be faced for Indonesian SMEs and in general the country's economy has also undergone terrible changes, then how can SMEs survive the current prolonged crisis due to the Covid-19 pandemic? This study aims to provide an understanding of how the customized configuration of various strategic initiatives can help Indonesian SMEs survive through the mass crisis based on the QHIM (Quadruple Helix Innovation Model) mechanism . Using a qualitative approach based on group discussions with the support of expert facilitators and involving parties from various fields, such as academia, banking, the entrepreneurial community and SMEs. SMEs operate in uncertain conditions, and some findings show that there has been an integration of various initiatives, such as financial resource management, opportunity exploration-exploitation, efficient negotiation, digital adoption and strategic management through balancing play an important role in terms of survival in crisis and how the Quadruple Helix perspective can become an important concept in the survival process of Indonesian SMEs.